Application of two-phase pulsating flow in organic Rankine cycle system for diesel engine waste heat recovery. (15th March 2022) - Zhang, Wujie; Yang, Fubin; Zhang, Hongguang; Ping, Xu; Yan, Dong; Wang, Chongyao
Abstract: Organic Rankine cycle is a promising technology to recover the waste heat of an internal combustion engine. Improving evaporator performance plays a vital role in achieving high heat to power conversion efficiency of this system. The circulating flow of working fluid in the system is realized by a pump, which is beneficial to heat transfer enhancement of the evaporator with pulsating flow. In this study, a two-dimensional axisymmetric model of evaporator tube is built. Two-phase flow characteristics of R245fa under continuous and pulsating flows are analyzed. Furthermore, particle swarm optimization (PSO) is employed to optimize the parameters of pulsating flow when diesel engine (DE) is operating under the motorway road condition. Results show that the heat transfer performance of R245fa can be improved effectively by the pulsating flow with a high angular frequency. Critical angular frequency, which enhances the heat transfer, exists. It also has a weak influence to flow performance. Compared with those in continuous flow under the motorway road condition of DE, the average convective heat flux and the volume fraction of R245fa vapor at the outlet optimized by PSO can be increased by 158.11% and 87.24%, respectively, whereas the pressure drop can be decreased by 1.47%. Highlights: Heat transfer performance can be significantly enhanced by pulsating flow. Sinusoidal pulsating flow has less effect on R245fa than square wave. Performance of pulsating flow combines with road condition of DE is studied. Optimal parameters of two-phase pulsating flow are obtained by PSO algorithm.